Menyoal Pengaturan Konsumsi Minuman Beralkohol di Indonesia - Puji Lestari, Tri Rini (Jurnal Aspirasi, 2016)
ThThe habit of consuming alcoholic beverages (modern, traditional or bootleg) can cause negative effects on physical, mental, and psychosocial healths. The problem of this research is related to regulation on the consumption of alcoholic beverages that is still not specific and not comprehensive. The purpose of this study is to gathered information on the consumption of alcoholic beverages and the enforced regulation, as well as a more specific and comprehensive concept on regulation regarding the consumption of alcoholic beverages so that people could be protected from the negative effects of the alcohol. This study uses qualitative descriptive study of literature and policy analysis with a formal evaluation approach. The results showed that there are some Indonesian who have a habit of consuming alcoholic beverages. The impact can cause physical, mental, as well as psychosocial health problems, and it can even takes one’s life (especially bootleg alcohol) thus disturbing the public. The regulation is currently still enforced over several different levels against several sectoral charges related to industry, investment, business licenses, alcoholic beverages, the imposition of customs, crime as the effects of consuming alcoholic beverages. Therefore future regulation should be more focused on the efforts to protect the public from negative effects of alcohol consumption with consideration on various factors from production to consumption.Kebiasaan mengonsumsi minuman beralkohol (modern, tradisional ataupun oplosan) dapat menimbulkan efek negatif baik secara fisik, mental, maupun psikososial. Permasalahan penelitian ini adalah pengaturan terkait konsumsi minuman beralkohol masih belum spesifik dan komprehensif. Tujuan penelitian adalah untuk mendapatkan informasi tentang konsumsi minuman beralkohol dan pengaturan yang ada selama ini, serta konsep pengaturan ke depan terkait konsumsi minuman beralkohol yang lebih spesifik dan komprehensif agar masyarakat dapat terlindungi dari efek negatif minuman beralkohol. Penelitian menggunakan metode deskriptif kualitatif dengan studi literatur dan dilakukan analisis kebijakan dengan pendekatan evaluasi formal. Hasil penelitian menunjukkan ada sebagian masyarakat Indonesia yang mempunyai kebiasaan mengonsumsi minuman beralkohol. Pengaturan yang ada masih tersebar di beberapa tingkat peraturan perundang-undangan dengan muatan pengaturan masih sektoral. Untuk itu, pengaturan ke depan harus lebih difokuskan pada upaya perlindungan masyarakat dari efek negatif konsumsi minuman beralkohol dengan memerhatikan berbagai faktor mulai produksi sampai dikonsumsi.